RELATIONSHIP BETWEEN PERSONALITY TRAITS AND SOCIAL ENTREPRENEURSHIP LEVELS OF PROSPECTIVE TEACHERS (Third Sector Social Economic Review, 2021)
The aim of this study is to investigate how and to what extent the personality traits of prospective teachers affect their social entrepreneurship traits. The research was designed according to the screening model and two Likert type scales were used. This study was conducted with 490 prospective teachers studying in different departments of Necmettin Erbakan University education faculty located in Konya in Turkey. As a result of the research, it was observed that compatibility and conscientiousness traits were more dominant among prospective teachers’ personality traits. It was determined that extraversion, conscientiousness and openness among personality traits were more effective on the prospective teachers’ perceptions of social entrepreneurship.
Keywords: Entrepreneurship; Social Entrepreneurship; Personality Traits; Prospective Teachers; Higher Education.